2014
DOI: 10.5120/16633-6502
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Object Recognition from Satellite Images using Artificial Neural Network

Abstract: Object recognition from satellite images is a very important application for various purposes. Objects can be recognized based on certain features and then applying some algorithm to extract those objects. Basically object recognition is a classification problem. For various remote sensing applications, waterbody acts as an important object which needs to be extracted. It is wise and better if possible, to extract waterbody object automatically from satellite data without any human intervention. This can be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…ANN is based on the biological structure of the neurons and their connections in living organisms [2]. It is a massively parallel distributed processor that has a natural propensity for storing experiential knowledge in inter-neuron connection strengths known as synaptic weights by a learning process and making it available for use for prediction [1]. Neurons are arranged in various layers that include an input layer, hidden layers, and an output layer [3].…”
Section: Theoretical Framework 21 Multi Layer Perceptron (Mlp) and Ementioning
confidence: 99%
See 2 more Smart Citations
“…ANN is based on the biological structure of the neurons and their connections in living organisms [2]. It is a massively parallel distributed processor that has a natural propensity for storing experiential knowledge in inter-neuron connection strengths known as synaptic weights by a learning process and making it available for use for prediction [1]. Neurons are arranged in various layers that include an input layer, hidden layers, and an output layer [3].…”
Section: Theoretical Framework 21 Multi Layer Perceptron (Mlp) and Ementioning
confidence: 99%
“…MLP is trained using training data before it is applied for prediction [3] and this training is supervised learning where prior information of desired response is known [1]. There are various algorithms proposed for the training of MLP but EBP algorithm is being used widely [4].…”
Section: Figure 1: Mlp Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, [20,21,22] used ANNs to identify green canopy cover from background soil and shadows. ANNs have also been used successfully to map water bodies [23] and flood extent [24]. However, to the authors’ knowledge the usefulness of ANNs in the classification of river features as part of hydromorphological assessment has not been tested yet.…”
Section: Introductionmentioning
confidence: 99%
“…Lippit et al [64] applied MLP to map selective logging sites in deciduous and mixeddeciduous forest in Massachusetts and Li et al [65] and Jensen et al [66] for forest age estimations; Chaudhuri and Parui implemented MLP [67] in defense application to identify target objects. Goswami et al [68] have shown the strength of MLP to identify objects in an image automatically. Their research shows that the perceptron can be effectively used to extract water bodies from satellite data with good accuracy.…”
Section: Introductionmentioning
confidence: 99%